2024
DOI: 10.3390/cancers16020270
|View full text |Cite
|
Sign up to set email alerts
|

MR-LINAC, a New Partner in Radiation Oncology: Current Landscape

Abrahams Ocanto,
Lisselott Torres,
Miguel Montijano
et al.

Abstract: Technological advances in radiation oncology are oriented towards improving treatment precision and tumor control. Among these advances, magnetic-resonance-image-guided radiation therapy (MRgRT) stands out, with technological advances to deliver targeted treatments adapted to a tumor’s anatomy on the day while minimizing incidental exposure to organs at risk, offering an unprecedented therapeutic advantage compared to X-ray-based IGRT delivery systems. This new technology changes the traditional workflow in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Currently, prostate tumors [5] and pancreatic tumors [6] emerge as locations with the most significant benefit and experience from guided adapted approaches, though the list continues to grow. Reports are promising, with minimal acute toxicity rates that do not impact the quality of life and confirm reasonable local control [4]. In this study, we prospectively evaluate the feasibility and acute toxicity of patients undergoing hypo-fractionated radiotherapy on a 0.35T MR-LINAC.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, prostate tumors [5] and pancreatic tumors [6] emerge as locations with the most significant benefit and experience from guided adapted approaches, though the list continues to grow. Reports are promising, with minimal acute toxicity rates that do not impact the quality of life and confirm reasonable local control [4]. In this study, we prospectively evaluate the feasibility and acute toxicity of patients undergoing hypo-fractionated radiotherapy on a 0.35T MR-LINAC.…”
Section: Introductionmentioning
confidence: 97%
“…This is due to the limited tolerance of organs at risk (OARs) to ionizing radiation and the significant mobility of structures such as ultra-central lung tumors or those in the upper abdomen. Further clinical studies are waiting for other locations where dose escalation has shown promising clinical advantages [3,4]. Currently, prostate tumors [5] and pancreatic tumors [6] emerge as locations with the most significant benefit and experience from guided adapted approaches, though the list continues to grow.…”
Section: Introductionmentioning
confidence: 99%